(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the knowledge, attitude and practices of people of Karachi regarding myths in dentistry. Study Design: Observational / Descriptive / Cross sectional study. Place and Duration of Study: This study was conducted at the OPD of Karachi Medical and Dental college and citizens of Karachi January 2015 – June 2015. Materials and Methods: The sample size was 150. Patients were recruited through convenience sampling. Data regarding myths in dentistry was recorded on a predesigned proforma. Data was analyzed using SPSS 17.00. Results: Results of the study shown that people with elderly age i.e. 39-50 years and with illiterate and primary level of education are most commonly involved in myths regarding dentistry. Females are the most common respondents involved in dental myths. Conclusion: It has been concluded from the study that dental myths are common facet of our community. There is a need to carry out community awareness programmes in order to teach and guide the community for these misconceptions.